Robust fixed-order H ∞ controller synthesis for multi-phase converters with input voltage feed-forward - Keskin, Ridvan; Aliskan, Ibrahim; Das, Ersin (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Generated DC voltages of batteries, fuel cells, or supercapacitors as power sources connected in series with DC-DC converters change according to operating conditions. In such cases, the output voltage stability of the multi-phase DC-DC converters is an issue, particularly being subject to noises in the input voltage and load current disturbances. Input voltage feed-forward (IVFF) compensation approaches can improve the output voltage stability of the DC-DC converters in such scenarios. This paper proposes a robust fixed-order H & INFIN; based IVFF control framework by considering sensor noise, input voltage, and load current disturbances to improve output voltage stability and reference tracking performance. The mismatched disturbance transfer functions depending on parasitic resistances are derived to include in the controller synthesis process. An iterative convex-concave optimization-based robust fixed-order controller design algorithm is proposed to optimize the feedback and feed-forward controllers under the stability and performance constraints. This algorithm allows the designing of the controllers simultaneously. The feed-forward controller, whose structure is independent of the system transfer functions, is optimized without any model inversion or extra design steps. The performance of the proposed controller is compared with an integral linear quadratic regulator controller, a sliding mode PID controller augmented with a nonlinear disturbance observer, and a fixed-order robust controller designed with non-smooth techniques. Real-time implementation of the fixed-order control systems is performed on a 2-leg 200 W interleaved boost converter. The performances are discussed under external disturbance effects to show the validity of the proposed control approach.& COPY; 2023 The Franklin Institute. Published by Elsevier Inc. All rights reserved.
Keywords: DC BOOST CONVERTER; DESIGN; FEEDBACK; SYSTEMS; STABILIZATION; OBSERVER; MODEL; Automation & Control Systems; Engineering; Mathematics